Legume Overseeding along with P Fertilization Increase Forage Production of Temperate Natural Grasslands - Rama, Gonzalo (2022)
Legume overseeding along with P fertilization is a common practice used in natural temperate and subtropical grasslands to increase forage production. This practice has been evaluated at experimental plots but not at the paddocks level of commercial farms. The latter are realistic evaluation units to generate knowledge for livestock management. In this study, the enhanced vegetation index (EVI), a proxy of forage production, was used to evaluate the effect of this practice on grazed paddocks in Uruguay. Twenty paired paddocks under similar grazing conditions were selected with natural grassland (NG) and natural grassland with legume overseeding and P fertilization (NG-LP). Paired paddocks were compared in terms of EVI mean and its temporal variability. After nine years of the intensification practice, mean annual EVI of NG-LP was 4% higher than that of NG, while the mean winter–spring EVI of NG-LP was 7.5% higher. EVI intra- and inter-annual variability of NG-LP was 8–11% higher than that of NG. Additionally, forage production was estimated using a radiative transfer model. Differences between NG-LP and NG were amplified six to seven times. Legume overseeding along with P fertilization increased forage production in pastoral livestock paddocks, particularly in the period of forage deficit, while it also increased intra and inter-annual variability of forage production.